Diffusion of LTACs output to Innovahub actors - Martínez, Jesús David; Borrayo, Andrea; García Santiago, Jorge O.; Loon, Jelle van (CGIAR System Organization, 2023)
The Local Climate Advisory Committees (LTACs) are spaces for inclusive dialogue between a diversity of local stakeholders such as farmers, extension services, representatives of the public, private and scientific sectors that seek to understand the possible behavior of the climate in a locality and generate recommendations to reduce the risks associated with expected climate variability. In Guatemala, following this dialogue, the agroclimatic bulletin is produced that comprises the weather forecast provided by the National Institute of Seismology, Volcanology, Meteorology, Meteorology and Hydrology. This report not only details the weather forecast, but also its possible influence on crops under specific weather and site conditions. It also offers recommendations to guide decisions within each regional production system. In Mexico the MTA methodology, arrived in 2019 starting in the state of Chiapas and with the accompaniment of the Bioversity Alliance - CIAT and CIMMYT, with the participation of different institutions leading actions such as the Ministry of Agriculture, Livestock and Fisheries (SAGYP) of the government of Chiapas and the Ministry of Agriculture and Rural Development (SADER) at the federal level. From 2019 to 2023 the SADER, led by the Climate Change Directorate has taken the AWM methodology to 12 states in Mexico. One of the bottlenecks that has been identified (cf. scaling workshop in Innovahubs 2022) in this methodology is the dissemination of information to a greater number of producers, specifically the agroclimatic bulletins that are generated through the MTA sessions. Therefore, a survey was constructed to learn how partners in Guatemala have shared agroclimatic information during the year 2023. And for Mexico, support was provided to SADER to implement a survey to find out the main problems, usefulness and means of dissemination that users recommend improving the dissemination and scope of the bulletins. During the hub meetings in Guatemala and Honduras in 2022, many farmers mentioned not to have access to the information and often did not completely understand. For this, during 2023, work was done to better understand the dynamics of how the information is spread and who uses the generated bulletins, with the objective to amplify its reach and function with the Innovahub members. This document reports on this analysis, showing that indeed mostly farm advisors and technicians consult the information. The bulletin is mostly distributed to users by WhatsApps groups or during local workshops. IN conclusion, it appears that the diffusion in Guatemala remains quite limited to certain regions, but people, as well in Mexico, report that the information is especially useful for planning the upcoming production cycle.